Associação entre exposição ao material particulado e internações por doenças respiratórias em crianças - Gobbo Cesar, Ana Cristina; Nascimento, Luiz Fernando C.; Carvalho, Joao Andrade de [UNESP] (Revista de Saúde Publica, 2013)
The aim of this study was to estimate the association between exposure to particulate matter less than 2.5 microns in diameter and hospitalization for respiratory diseases. It was an ecological time series study with daily indicators of hospitalization for respiratory diseases in children up to 10 years, living in Piracicaba, SP, Southeastern Brazil, between August 1, 2011 and July 31, 2012. We used generalized additive model for the Poisson regression. The relative risks were RR = 1.008; 95%CI 1.001; 1.016 for lag 1 and RR = 1.009; 95%CI 1.001; 1.017 for lag 3. The increment of 10 mu g/m(3) in particulate matter less than 2.5 microns in diameter implies increase in relative risk between 7.9 and 8.6 percentage points. In conclusion, exposure to particulate matter less than 2.5 microns in diameter was associated with hospitalization for respiratory diseases in children.
Association between exposure to particulate matter and hospital admissions for respiratory diseases in children
Keywords: Pneumonia; Asthma; Respiratory Tract Diseases; Air Pollutants; Air Pollution; Particulate Matter; Child Health; Time Series Studies